Perceptions of Accounting Taxation Students Toward the Use of Artificial Intelligence (AI) in Industry Settings: A Descriptive Survey - Abdi Bhayangkara; Junaldo Rizky Mirza (Jurnal Ilmiah Raflesia Akuntansi, 2026)
This study aims to explore how Tax Accounting students currently undergoing internships perceive and respond to the use of Artificial Intelligence (AI) in the industries where they are placed. As AI becomes increasingly integrated into accounting and business processes, understanding how students experience these technologies in real work settings is crucial. Using a descriptive quantitative method with a survey approach, this study collected responses from 118 students through an online questionnaire. The instrument consisted of 14 closed-ended statements adapted from previous research related to AI awareness, perceived usefulness, and readiness for technological adoption. Data were analyzed using descriptive statistics to identify trends in students’ awareness, understanding, and attitudes toward AI implementation in their internship environments. The results are expected to provide insights into how well academic learning aligns with the technological realities of modern accounting practices and to highlight areas where further training or curriculum development may be necessary to prepare future professionals for an AI-driven industry